Implementation of COBIT 2019 with Domain DSS01, DSS03, and MEA01 for Audit of Customer Water Usage Recording Information System at HIPPAM Mandiri Arjowinangun - Nadira, Reva Rahma; Mawaddah, Hilmiyah; Tirtana, Arif (IC-ITECHS, 2024)
Currently, HMA faces challenges in optimizing the recording system, because the meter recording process is still done manually. This manual process hampers operational efficiency and data accuracy which impacts the quality of service to customers. Therefore, it is necessary to evaluate the existing information system to measure whether the application of information technology is in accordance with the goals and expectations of the organization. This study aims to analyze the application of information technology in HMA using the COBIT 2019 framework, specifically in the domains DSS01 (Manage Operations), DSS03 (Manage Problems), and MEA01 (Monitor, Evaluate, and Assess Performance). Through capability analysis in these three domains, this study identifies gaps in the existing system and provides recommendations for improvements to improve the efficiency and accuracy of the customer water usage recording system. The results of the study indicate that HMA's capability level is still below the desired target, so it is important to make improvements by implementing more integrated digital solutions and improving continuous monitoring and evaluation of system performance.